A prospective study on serum Cytokeratin (CK)-18 and CK18 fragments as biomarkers of acute hepato-intestinal GVHD. Issue 12 (December 2018) - Sauer, Sandra; Hüsing, Johannes; Hajda, Jacek; Neumann, Frank; Radujkovic, Aleksandar; Ho, Anthony; Dreger, Peter; Luft, Thomas
Abstract Apoptotic intestinal crypt cells are pathognomonic of acute intestinal graft versus host disease (GVHD). Serum levels of the apoptotic degradation product cytokeratin-18 fragments (CK18F) were associated with acute hepato-intestinal GVHD. Here we present a prospective clinical observational trial (NCT00935324) investigating serum levels of total CK18 (tCK18) and apoptotic CK18F to predict imminent acute hepato-intestinal GVHD and response to treatment. Total (t)CK18 and CK18F kinetics were measured before transplantation and in weekly intervals thereafter. In total 109 patients were enrolled. Acute hepato-intestinal GVHD grade I–IV was suspected in 36 patients (33%) at a median of 56 days post-transplant, 12 of these patients developed steroid-refractory GVHD. Both tCK18 and apoptotic CK18F increased at GVHD onset, and distinguished patients with suspected acute hepato-intestinal GVHD who were negative in intestinal histology. In patients with clinical acute hepato-intestinal GVHD, tCK18 significantly raised already 7–14 days before symptom onset. In receiver operator characteristics, areas under the curve at GVHD onset were 0.927 (p < 0.001) for tCK18 and 0.875 (p < 0.001) for apoptotic CK18F for patients with proven hepato-intestinal acute GVHD. This prospective study validates CK18F and highlights tCK18 as specific biomarkers suitable for improving prediction and diagnosis of suspected imminent and clinically manifest acute hepato-intestinal GVHD.